Contribution of treatment acceptability to acceptance of randomization: an exploration. Issue 1 (23rd July 2015) - Sidani, Souraya; Fox, Mary; Epstein, Dana R.
Abstract: Rationale, aims and objectives: Randomization to treatment is viewed unfavourably by many trial participants. There is limited research that investigated factors contributing to acceptance of randomization. This study explored the influence of participants' socio‐demographic and clinical characteristics, and their perceived acceptability of the treatments on their acceptance of randomization (i.e. willingness to be randomized) in a clinical trial. Methods: Persons with insomnia ( n = 383) were asked about their acceptance of randomization before and after they rated the acceptability of behavioural therapies for managing insomnia (sleep education and hygiene booklet, stimulus control therapy and sleep restriction therapy). Socio‐demographic and clinical characteristics, and treatment acceptability, were measured with established instruments. Logistic regression was applied to explore the association between participants' characteristics and treatment acceptability, and reported acceptance of randomization. Results: Prior to rating treatments' acceptability, 54.6% of participants were willing to be randomized; socio‐demographic (age and ethnicity) and clinical (severity of insomnia's impact, state anxiety, depression, vitality and mental and social functions) contributed to acceptance of randomization. After rating the treatments' acceptability, 87.8% of participants were unwilling to be randomized; age, severity of insomnia's impact and acceptability of behavioural therapy were significantly associated with acceptance of randomization. Conclusions: The study findings indicated that participants are likely to express unwillingness to be randomized once they receive treatment information and rate the acceptability of treatments. The reported non‐acceptance may influence participants' behaviour (e.g. withdrawal, non‐adherence) during the trial, suggesting the need to explore alternative designs for intervention evaluation.